Sublimation and Diffusion Kinetics of 2,4,6-Trinitrotoluene (TNT) Single Crystals by Atomic Force Microscopy (AFM) - Walid M. Hikal; Sanjoy K. Bhattacharia; Mark W. Vaughn; Brandon L. Weeks (Molecules, 2022)
In this article, we report the in-situ nanoscale experimental measurement of sublimation rates, activation energy of sublimation, and diffusion coefficients of 2,4,6-trinitrotoluene (TNT) single crystals in air using atomic force microscopy (AFM). The crystals were prepared by slow evaporation at 5 °C using acetone-dissolved TNT. The mass loss was calculated by monitoring the shrinkage of the surface area of layered islands formed on the surface of the TNT crystals due to sublimation upon isothermal heating at temperatures below the melting point. The results suggest the sublimation process occurs via two-dimensional detachment of TNT molecules from the non-prominent facets on the crystal surface which imitates the nucleation and crystal growth process. Sublimation rates are one order of magnitude smaller than previously reported values. However, the calculated activation energy (112.15 ± 3.2 kJ/mol) and temperature-dependent sublimation rates agree well with the reported values for TNT thin films and microcrystals determined by UV-vis absorbance spectroscopy and quartz crystal microscopy (QCM) (90–141 kJ/mol). The average diffusion coefficient is (4.35 × 10–6 m2/s) which is within the range of the reported theoretical values with an average of 5.59 × 10–6 m2/s, and about 25% less than that determined using thermogravimetric analysis for powder TNT.